Objectives in Higher Education - Beard, Ruth M.; Society for Research into Higher Education, Ltd., London (England). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
This is the first in a series of books that will deal with different aspects of teaching and learning in higher education, such as students' learning and individual differences, teaching methods, and new teaching techniques. Four papers examine general objectives in higher education and relate them to techniques of evaluation and teaching methods. The papers acknowledge that some recent modifications of curricula and methods arise from considerations of certain objectives in university teaching, but attempt to demonstrate that a more detailed analysis of purposes and aims in teaching would not only be profitable but will soon become essential. Whether objectives are likely to be realized or not depends on a number of factors, including the way in which they are evaluated, the processes employed in learning, and the consonance of objectives with the needs and abilities of students and with the requirements of the society in which students live. These factors are surveyed in the first paper. The second discusses the evolution of educational objectives in European universities of the nineteenth and twentieth centuries. The third outlines some approaches to more detailed analyses of specific objectives, and the final paper discusses some problems of evaluating objectives in an effective way. (WM)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Trends; Teacher Responsibility; Educational Objectives; Evaluation Methods; Higher Education; Learning Processes; Teaching Methods; Great Britain